Evaluation of the relationship of Delta-CO2 with IVC-CI, IJV-CI, and CVP values in intubated critically ill patients with spontaneous breathing, and who were applied invasive mechanical ventilation in CPAP mode - Kivilcim Kacar, Cem; Uzundere, Osman; Bicak, Mustafa; Kandemir, Deniz; Kaya, Sedat; Yektas, Abdulkadir (Annals of Medical Research, 2021)
Aim: Our aim in this study is to understand whether there is a correlation between IVC-CI, IJV-CI, CVP, and Delta-CO2 values in critical patients in the ICU and whether these values can be used interchangeably in monitoring intravascular fluid status.. Materials and Methods: Patients included in this study were selected from critical ICU patients between 18-90 years old with an unknown hypovolemic status that had spontaneous breathing and underwent invasive mechanical ventilation in CPAP mode. Patients’ parameters were consecutively measured by USG with the inferior vena cava collapsibility index (IVC-CI), internal jugular vein collapsibility index (IJV-CI), CVP, and Delta-CO2. The results were recorded, and any correlations were checked.Results: There was a statistically significant and moderately negative correlation (r = -0.428, p 0.001) between CVP and IVC-CI, and a statistically significant and weakly negative correlation between CVP and IJV-CI (r = -0.374, p = 0.001). There was a statistically significant and weakly positive correlation (r = 0.369, p = 0.001) between IVC-CI and IJV-CI. There was no statistically significant correlation between Delta-CO2 and IVC-CI, IJV-CI, and CVP.Conclusion: We think that CVP, IVC-CI and IJV-CI can be used interchangeably in the assessment of the intravascular volume status of critical patients, but Delta-CO2 cannot be used to assess intravascular volume status instead of these parameters.